Exploring agroforestry limiting factors and digitalization perspectives: insights from a european multi-actor appraisal - Tranchina, Margherita; Burgess, Paul J.; Cella, Fabrizio Giuseppe; Cumplido-Marin, Laura; Gosme, Marie; den Herder, Michael; Kay, Sonja; Lawson, Gerry; Lojka, Bohdan; Palma, João H. N.; Pardon, Paul; Reissig, Linda; et al. (Springer, 2024)
Despite its potential for fostering farm sustainability, the adoption of agroforestry faces context-dependent challenges, among which the (perceived) shortage of decision-supporting tools and barriers hindering the assessment of economic, environmental, and social benefits. The process of digitalization offers significant opportunities to enhance sustainability, but it remains crucial to foster a human-centric, fair, and sustainable approach. In the context of the DigitAF Horizon Europe project, we present the results of a multi-stakeholder questionnaire aimed at understanding the perceptions of stakeholders regarding agroforestry and digitalization, as well as the needs of these stakeholders for a successful implementation of this agricultural practice. In the questionnaire, there was a specific focus on the need for and the conditions for the use of digital tools and models, such as generalized digital tools, applications and mapping, climate and weather forecasting and recording, farm management and decision support, and agroforestry and environmental tools. The purpose of this survey was to provide insights to inform agroforestry actors and to foster collaborative initiatives that enhance the potential of digital tools to support the design, implementation, and maintenance of effective and sustainable agroforestry in the European context. Our questionnaire was completed by stakeholders from seven European countries, including farmers, academics, policy actors, farm advisors, and actors in the value chain with an interest in agroforestry. Stakeholders from six living labs, representing Czechia, Finland, Germany, Italy, the Netherlands, and the UK, were involved in the appraisal, along with a multi-stakeholder group from Belgium. Respondents used data and digital tools for various purposes in farming systems and were interested in their potential to improve agroforestry including animal, tree, and crop performance, management guidance, system design, and tree species selection. Our survey revealed that the perceived usefulness of digital tools for agroforestry was substantially higher than stakeholders' awareness of existing tools, indicating a need for better promotion and development of user-friendly, accessible solutions. Additionally, significant obstacles to agroforestry adoption, such as large up-front investments, administrative burdens, and fear of reduced CAP support, were identified, emphasizing the necessity for targeted support and policy improvements. Moving forward, efforts should focus on developing targeted solutions to promote agroforestry according to stakeholder perception, and user-friendly digital tools tailored to the needs and preferences expressed by stakeholders, while also increasing knowledge sharing and capacity building among practitioners and researchers.
Keywords: Stakeholder perception; Participatory research; Actor-oriented research; Sustainable agriculture; Tools; Survey; 30 Agricultural, Veterinary and Food Sciences; 15 Life on Land; Forestry